READING ATTITUDE AND READING INTEREST OF STATE JUNIOR HIGH SCHOOL STUDENTS TOWARD THEIR FUNCTIONAL READING ACHIEVEMENT - Yustika, Retno Indri (Universitas Muhammadiyah Metro, 2025)
Despite growing emphasis on reading literacy in educational policy, limited attention has been given to the specific contributions of reading attitude and reading interest to students’ functional reading achievement (FRA), particularly among junior high school learners. This study examines the relationship between various aspects of reading attitude and interest and students’ FRA, providing empirical insights from a less-explored context. The objectives were to examine students’ FRA, reading attitude, and reading interest; the correlations among these variables; and the extent to which attitude and interest contribute to FRA. Data were collected through the Functional Reading Achievement Test (FRAT) and the Attitude Toward and Interest in Reading Literacy (ATIReaL) questionnaire, administered to 237 students at state junior high schools in Seberang Ulu 1 and 2, Palembang. Results indicated that students’ FRA was very low (mean = 41.78), with no significant difference between male and female students. While students generally showed a positive attitude toward reading, their reading interests varied. Correlation analysis showed no significant relationship between total scores of FRA and total scores of reading attitude or interest. However, two specific attitude components and 17 interest components were significantly correlated with FRA. Among them, seven interest items and two attitude items significantly contributed to FRA. The highest contribution came from interest in another language (6.1%) and the attitude of reading to learn new things (5.2%). These findings suggest that although overall reading disposition may not directly predict FRA, certain specific interests and attitudes play a meaningful role in shaping students’ reading performance.